Xi Jinping, the governance of China. - Xi, Jinping (China Foreign languages press, 2014)
"As general secretary of the CPC Central Committee and president of the People's Republic of China, Xi Jinping has delivered many speeches on a broad range of issues. He has offered his thoughts, views and judgments, and answered a series of important theoretical and practical questions about the Party and the country in these changing times. His speeches embody the philosophy of the new central leadership. To respond to rising international interest and to enhance the rest of the world's understanding of the Chinese government's philosophy and its domestic and foreign policies, the State Council Information Office, the Party Literature Research Office of the CPC Central Committee and the China International Publishing Group have worked together to produce this book. The book is a compilation of Xi Jinping's major works from November 15, 2012 to June 13, 2014. It includes, speeches, talks, interviews, instructions, and correspondence for a total of 70 pieces. It also contains 45 pictures of Xi Jinping at work and in daily life with focus on the period since the 18th National Congress of the Communist Party of China in 2012"--Publisherʹs note.
Issued also in Arabic, Chinese, French, German, Japanese, Portuguese, Russian, and Spanish simultaneously.
Includes bibliographical references and index.
Keywords: Nationalism -- China; World politics -- 21st century; Political oratory -- China -- 21st century; China -- Politics and government -- 2002-; China -- Foreign relations -- 21st century